STUDENTS’ WRITING ABILITY IN NARRATIVE PARAGRAPH AT THIRD SEMESTER OF ENGLISH EDUCATION PROGRAM OF STKIP YPM ACADEMIC YEAR 2020/2021 - Herysa Oktawati; Efa Silfia (Politeknik Negeri Bengkalis, 2020)
: Writing is the highest level in mastering of language after listening, speaking, and reading. It is unnatural act which is difficult, but it can be learned through practice continuously and intensively. In real condition, students have problem with writing, they were not comprehensible because the content of the composition was not relevant to the topic, the ideas were not clearly stated, the ideas and sentences were not well organized. The aim of this research is to find out the ability of the third semester students of English Department of STKIP YPM in writing a narrative paragraph. This research was descriptive quantitative method. It was done to find out the students’ ability in writing narrative paragraph. It was used in this research because in descriptive research the researcher has been described the events and indications. Meanwhile, quantitative approach was used to give the numeric in analyzing the data, give the table, and calculate the students’ numbers or points. Population of this research was the third semester students English Department of STKIP YPM Bangko. The researcher used total sampling in taking the sample because the total of population was 28 students. The instrument used to collect data in this research was written test. Based on the research finding and data analysis, it can be concluded that students’ ability in writing narrative paragraph. Based on the research finding and data analysis, it can be concluded that students’ ability in writing narrative paragraph, A was 2 students, A- was 4 students, B+ was 3 students, C+ was 8 students, C was 6 students, C- was 5 students. From the data above, 19 students had low score in qualification C+, C, and C-. Based on the table above, it can be seen the percentage of the students. It just 32 % students who got high score, but 68% students who got low score. It means that the higher of of percentage of the students’ ability who did not understand in writing narrative paragraph.